Daniil Isaakovich Goldberg (1906—1973). To the 100th anniversary - V. V. Novitsky; S. F. Fominykh; V. S. Lavrova; S. A. Nekrylov; M. V. Gribovsky (Бюллетень сибирской медицины, 2006)
2006 is the 100th anniversary of the great Russian scientist-pathophysiologist, outstanding representativeof the Tomsk school of pathophysiologists, honoured scientist of Russia, professor of the Tomsk Medical Institute Daniil Assakovich Goldberg (1906—1973). Creative biography of the scientist and main directions of his scientific activity are described in the article.